2019
DOI: 10.3390/v11110998
|View full text |Cite
|
Sign up to set email alerts
|

Npro of Classical Swine Fever Virus Suppresses Type III Interferon Production by Inhibiting IRF1 Expression and Its Nuclear Translocation

Abstract: Classical swine fever virus (CSFV) causes a contagious disease of pigs. The virus can break the mucosal barrier to establish its infection. Type III interferons (IFN-λs) play a crucial role in maintaining the antiviral state in epithelial cells. Limited information is available on whether or how CSFV modulates IFN-λs production. We found that IFN-λ3 showed dose-dependent suppression of CSFV replication in IPEC-J2 cells. Npro-deleted CSFV mutant (∆Npro) induced significantly higher IFN-λs transcription from 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 65 publications
2
16
1
Order By: Relevance
“…These results are not surprising when considering that CSFV targets specifically IRF3 for proteasomal degradation by means of N pro [8] while the TNF-induced anti-CSFV activity we observed in the PEDSV.15 cells was completely independent of IRF3 (Figure 3d). However, the lack of interference of CSFV with the IRF1-dependent pathway described here is in apparent contradiction with recent data showing that N pro of CSFV inhibits IRF1 expression and nuclear translocation in porcine intestinal epithelial IPEC-J2 cells, thereby suppressing type III IFN production [24]. This latter finding may, however, be a specific feature of IFN-λ producing cells.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These results are not surprising when considering that CSFV targets specifically IRF3 for proteasomal degradation by means of N pro [8] while the TNF-induced anti-CSFV activity we observed in the PEDSV.15 cells was completely independent of IRF3 (Figure 3d). However, the lack of interference of CSFV with the IRF1-dependent pathway described here is in apparent contradiction with recent data showing that N pro of CSFV inhibits IRF1 expression and nuclear translocation in porcine intestinal epithelial IPEC-J2 cells, thereby suppressing type III IFN production [24]. This latter finding may, however, be a specific feature of IFN-λ producing cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Importantly, the downstream antiviral effects of TNF were independent of the type III IFN antiviral pathway in the PEDSV.15 cells since there was a strict IFNAR1 requirement (Figure 3b). This may be different in other cell types such as intestinal epithelial cells that induce type III IFNs in an IRF1-dependent manner [24]. In the PEDSV.15 cells, we demonstrated that the TNF-triggered induction of IFN-β transcripts and the resulting antiviral effect rely on intact IRF1 (Figure 4b,d), whereas IRF3 was dispensable (Figure 3d).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Zika virus nonstructural protein NS5 was found to inhibit the RIG-I pathway and IFN-λ1 promoter activation by targeting IKKε [28]. Npro of classical Swine fever virus suppressed IFN-λ production by inhibiting IRF1 expression and its nuclear translocation [29]. In this study, we investigated whether lncRNA-AK097647 can play a role in host innate immunity during EV71 infection.…”
Section: Discussionmentioning
confidence: 99%